Caracterização agronômica de linhagens de pimenta roxas (Capsicum chinense) - Almeida, Isabelle Nogueira Fernandes de (Universidade Federal de São Carlos, 2025)
Capsicum peppers are distinguished by their wide diversity of shapes, aromas, and colors. The consumption of these peppers has been increasing both in Brazil and worldwide, establishing a promising market that involves various agricultural sectors. This stimulus has encouraged the search for new cultivars with varied characteristics and qualities. In pepper fruits, especially those displaying purplish hues, the characteristic coloration is due to the accumulation of anthocyanins in the epidermal and pulp cells. Anthocyanins are natural pigments belonging to the flavonoid class. Currently, purple-colored peppers are not available in the Brazilian market. For the development of these new cultivars, the characterization of accessions from germplasm banks is fundamental for future Capsicum genetic breeding programs. In this context, the present study was developed to perform the agronomic characterization of purple pepper genotypes from the Germplasm Bank of the Federal University of São Carlos, Araras campus. The experiment was conducted in a greenhouse, evaluating 8 C. chinense lines. Agronomic assessments were based on quantitative criteria, qualitative descriptors, and instrumental color analysis. The analysis of the results indicated that the Rh Lilac Black, Bode Roxa, Olho Mutum, and Rubro Black Multicolor lines stood out due to their good yield, important morphological and visual characteristics, and significant potential for integration into purple pepper breeding programs. Keywords: anthocyanin; genetic breeding.
Agronomic characterization of purple pepper lines (Capsicum chinense)
Keywords: Antocianina; Melhoramento genético; Anthocyanin; Genetic improvement; CIENCIAS AGRARIAS